(untitled) (Journal of Health Sciences, 2013)
Metastases to gastrointestinal tract are uncommon. In particular, metastases to the ampulla of Vater are very rare and may represent a significant diagnostic challenge. Metastases from the uterine cervix to the ampulla of Vater are exceedingly rare and only one case has been described in the available literature. We describe here a second case of metastatic squamous cell carcinoma of the cervix to the ampulla of Vater in a 45-year-old woman. Poorly differentiated squamous cell carcinoma presented as an isolated metastasis to the ampulla of Vater, two years after the initial diagnosis. While the squamous cell carcinoma could occur as primary ampullary carcinoma, albeit very rare, it is necessary to exclude the possibility of metastatic cancer.